Association of High Calcitriol Serum Levels and Its Hydroxylation Efficiency Ratio with Disease Risk in SLE Patients with Vitamin D Deficiency - Mónica R. Meza-Meza; José Francisco Muñoz-Valle; Adolfo I. Ruiz-Ballesteros; Barbara Vizmanos-Lamotte; Isela Parra-Rojas; Erika Martínez-López; Edith Oregon-Romero; Yolanda Fabiola Márquez-Sandoval; Sergio Cerpa-Cruz; Ulises de la Cruz-Mosso (Journal of Immunology Research)
Vitamin D (calcidiol) deficiency in systemic lupus erythematosus (SLE) is more frequent than in healthy subjects (HS); it is associated with clinical activity and damage in SLE. Although calcidiol is considered the best indicator of the vitamin D serum status, its deficiency could not reflect its hydroxylation efficiency ratio and calcitriol serum status. This study was aimed at assessing the association of calcidiol and calcitriol serum levels and its hydroxylation efficiency ratio with the risk to clinical and renal disease activities in SLE patients. A cross-sectional study was conducted in 308 SLE and HS women; calcidiol and calcitriol serum levels were evaluated by immunoassays. SLE patients showed lower calcidiol serum levels vs. HS (21.2 vs. 24.2 ng/mL; p<0.001). Active SLE patients presented higher calcidiol/calcitriol ratio scores vs. inactive SLE patients (2.78 vs. 1.92 pg/ng; p=0.02), and SLE patients with renal disease activity showed a pattern of calcidiol-deficient levels (19.5 vs. 25.3 ng/mL; p<0.04) with higher calcitriol levels (47 pg/mL vs. 41.5 pg/mL; p=0.02) and calcidiol/calcitriol ratio scores (2.13 vs. 1.54 pg/ng; p<0.02) compared to SLE patients without renal disease activity. Calcidiol levels were negatively correlated with calcitriol levels (r=−0.26; p=0.001) and urine proteins (mg/dL) (r=−0.39; p<0.01). Regarding calcitriol levels, it was positively correlated with the blood lymphocyte count (r=0.30; p<0.001) and negatively correlated with the glomerular filtration rate (r=−0.28; p=0.001). Moreover, the calcitriol/calcidiol ratio was positively correlated with urine proteins (r=0.38; p<0.01). The calcidiol deficiency (OR=2.27; 95% CI=1.15-4.49; p<0.01), high calcitriol levels (T3rd, OR=4.19, 95% CI=2.23-7.90; p<0.001), and a high calcitriol/calcidiol ratio score (T3rd, OR=5.93, 95% CI: 3.08-11.5; p<0.001) were associated with the risk for SLE. In conclusion, a pattern of calcidiol deficiency with high calcitriol serum levels and a high vitamin D hydroxylation efficiency ratio was associated with disease risk in SLE patients.